Does the association exist between the insulin aplication and malignancies – the literature review - Spych, Michał; Rychter, Anna; Fijuth, Jacek (Menopause Review/Przegląd Menopauzalny, 2009)
Although insulin has predominantly metabolic effects, it also has weak direct and indirect mitogenic properties. In a number of studies it has been postulated that diabetes mellitus is associated with an increased risk of mortality from a range of solid tumors, including cancers of the colon, breast and pancreas. Similar associations have been noted with obesity and other conditions associated with increased levels of circulating insulin. These observations have given rise to the hypothesis that growth of these tumors, which are characterized by abnormal expression and function of the insulin and IGF-1 receptors, is promoted by the trophic action of insulin interacting with these receptors. In 2009 a number of series has been published, in which potential association between insulin use and risk of malignant disease in patients with diabetes mellitus was demonstrated. In the study an accessible publications concerned the issue of the risk of malignancies in patients with diabetes treated with insulin has been reviewed.